BALKAN I EVROPSKE INTEGRACIJE - Račić, Mile (Poslovna ekonomija, 2017)
Abstract: Bosnia and Herzegovina, as the other Balkans countries, in its current development have been utilising the processess of institutionalization, transition and democratization to direct its further political and economic development towards the European Union. The Accession to the European Union is the result of a broad political consensus achieved at all levels of government: state and entity, while the commitment of the citizens of Bosnia and Herzegovina has been an important factor in this process, which has been confirmed by numerous surveys recently. The results achieved for EU accession have been confirmed in the Roadmap, the Feasibility Study and the Stabilisation and Association Agreement between the European Union and Bosnia and Herzegovina. Further steps of this process have been verified by the Action Plan for the implementation of the Reform Agenda adopted by the Council of Ministers. In the line with the Reform Agenda, BiH filed an application for EU membership on 15th February 2016. The application for membership was accepted by the authorities of EU on 20th September 2016 and accordingly the Questionnaire of the European Commission BiH was delievered. Bosnia and Herzegovina needs to respond to it and present the evidence of compliance with the conditions as it opens the way to obtaining the candidate status for EU membership and the opening of the negotiation process. Other Balkans countries that are on the path of European integration, each individually in direct negotiations with the Commission, Council and Parliament, have beeen implementing the negotiation process being, in that way, on the road to full membership in the European Union. Key words: political and economic system, democratization and European integration